Abordagem metalômica quantitativa de mercúrio em peixes da região amazônica - Queiroz, João Vitor de [UNESP] (2015)
This paper presents the results of mercury fractionation in muscle samples of tucunaré (Cichla spp.) and filhote (Brachyplatystoma filamentosum) from the JIRAU Hydroelectric Power Plant in the Madeira River Basin in the Amazon region of Brazil. The proteome of the fishes muscle was separated by two-dimensional polyacrylamide gel electrophoresis (2D PAGE). The mercury present in the protein spots was determined by graphite furnace atomic absorption spectrometry (GFAAS) after acid mineralization in an ultrasound bath. The protein spots in which the presence of mercury was detected were characterised by electrospray ionisation tandem mass spectrometry (ESI-MS/MS) after tryptic digestion. The GFAAS determinations indicated that 65% of the mercury was linked to the protein fraction with a molar mass (Mm) of less than 90 kDa. The mercury concentration in the eleven spots in this protein fraction was present were in the range 13.60 to 17.10 mg g-1. Based on mercury concentrations, it was possible to estimate that the protein spots contained approximately one atom of mercury per protein molecule. Analysis by ESI-MS / MS protein allowed the characterization of ten spots as proteins and / or following enzymes: parvalbumin-2 (MW = 12.40, pI = 3.80); parvalbumin alpha (Mm = 12.40, pI = 3.80); parvalbumin beta (Mm = 12.40, pI = 3.80); ubiquitin-40S ribosomal protein S27a (Mm = 11.60, pI = 6.10); GTP cyclohydrolase 1 regulatory protein of feedback (Mm = 13.00, pI = 4.00) and transmembrane protein 186 (Mm = 14.00, pI = 4.70).